The impact of precipitation on the variability of wastewater discharge from the area of Połaniec agglomeration - Karolina Elżbieta Hap; Ewa Dacewicz; Krzysztof Chmielowski (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of study was to determine the influence of precipitation on the variability of wastewater discharge from the wastewater treatment plant located in Łęg in Połaniec agglomeration.